Penerapan Gamifikasi Pada Media Pembelajaran Untuk Meningkatkan Aktivitas Dan Hasil Belajar Siswa - Kurnia Rahman Agus; Dadang Syarif Sihabuddin Sahid; Syabdan Dalimunthe (UIR PRESS, 2023)
The demands of the learning process during the current pandemic force teachers and students to carry out digital transformation in the learning process. Especially in the new normal where the learning process is done online. Thus, the learning media made by the teacher must also be adapted to online media so that the learning process can be maximized and increase the activeness of students in learning while online. This study aims to create an online learning media by applying the concept of gamification. The method used in this research is R&D (Research and Development) using analysis, design, and development development models. Stages of analysis are carried out to determine the needs of students when learning online. Then in the design stage, the selection of media formats and media design is carried out, and finally at the development stage, the advanced process of making games with programming languages is carried out as a learning medium. The use of gamification learning media is very practical, which can be accessed by students through their devices at home via the internet network. In the learning process, this game can be used to assist teachers in achieving learning objectives so that they can increase learning activity and the value of students in one basic competency.